2021
DOI: 10.1038/s41416-020-01252-2
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a biomarker candidate for surgical stratification in high-grade serous ovarian cancer

Abstract: Background Maximal effort cytoreductive surgery is associated with improved outcomes in advanced high-grade serous ovarian cancer (HGSOC). However, despite complete gross resection (CGR), there is a percentage of patients who will relapse and die early. The aim of this study is to identify potential candidate biomarkers to help personalise surgical radicality. Methods 136 advanced HGSOC cases who underwent CGR were identified from three public transcriptomic datasets. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Various findings have shown that ovarian cancer is associated with high mortality, and in most cases, it is diagnosed after the metastasis of cancer beyond the ovaries and often throughout the abdomen, which should be considered because early detection can lead to effective treatment and lower recurrence. [19][20][21] One of the limitations of this study was the small number of samples studied. During the 12 years of study, we tried to increase the sample as much as possible to a reasonable and measurable level.…”
Section: Discussionmentioning
confidence: 94%
“…Various findings have shown that ovarian cancer is associated with high mortality, and in most cases, it is diagnosed after the metastasis of cancer beyond the ovaries and often throughout the abdomen, which should be considered because early detection can lead to effective treatment and lower recurrence. [19][20][21] One of the limitations of this study was the small number of samples studied. During the 12 years of study, we tried to increase the sample as much as possible to a reasonable and measurable level.…”
Section: Discussionmentioning
confidence: 94%
“…DPM1, one of the relevant genes, is a vital sensor molecule related to the regulation of cytosolic Ca 2+ levels in the maintenance of B-cell functions and a potential prognostic tumor marker of HCC ( Li et al, 2020b ). ALG5 was reported as a prognostic biomarker for early tumor progression in advanced high-grade serous ovarian cancer (HGSOC) ALG5 ( Lu et al, 2021 ). A previous study indicated that ALG9 was regulated by lncRNA MEG3 and participated in the drug resistance mechanism in acute myeloid leukemia ( Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One such technology is microarray sequencing, in which mRNA counts are used to describe gene expression. Such data, known as transcriptomics, are widely used in the biomedical domain and when analyzed alongside survival times have provided extraordinary opportunities for biomarker characterization and prognostic modeling ( Bøvelstad et al , 2007 ; Lightbody et al , 2019 ; Lloyd et al , 2015 ; Lu et al , 2021 ). However, profiling data are often high-dimensional, which introduces several statistical challenges including: (i) variable selection, (ii) effect estimation of the features, (iii) uncertainty quantification and (iv) scalable computation.…”
Section: Introductionmentioning
confidence: 99%